Pemberdayaan Masyarakat Desa Melalui Pemanfaatan Media Sosial Sebagai Strategi Pemasaran Digital Dalam Peningkatan Penjualan Minyak Sereh - Laksana, Tri Ginanjar; Wibowo, Ariel Maulana; Pranoto, Imam Aji (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Digital Social Media Marketing (DSMM) or as it is known today, how to utilize social media networks in the form of digital marketing that uses social media platforms and social networking websites with the aim of increasing and gaining marketing and promoting an organization's products and services through paid or unpaid means. The use of social media as a marketing tool (Digital Marketing) has a big influence in increasing sales turnover and promotions. The aim of implementing this community service is how to increase sales of lemongrass oil products that have been made and are currently being marketed by utilizing digital marketing strategies. The current marketing and promotion of lemongrass oil products carried out by the community, especially PKK women, Sekarwangi Village, Cibadak District, Sukabumi Regency, is currently still conventional. Policy makers, society and academics should be able to overcome these problems. Many of the citronella oil products processed by PKK women have not been sold, resulting in citronella oil products piling up and experiencing losses. The parties involved in empowerment must be able to provide power and encouragement to the community to improve marketing strategy skills so as to create community creativity in marketing and product promotion to increase sales Sereh Oil.